2022
DOI: 10.3389/fonc.2021.780387
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Mechanisms by Which Quercetin Enhances Cisplatin Action in Cervical Cancer: A Network Pharmacology Study and Experimental Validation

Abstract: Yimucao has been used as an herbal medicine to treat gynecological diseases. Common genes of Yimucao active compounds were investigated using network pharmacology. The components and targets of Yimucao were retrieved from the TCMSP database. Cervical cancer targets were collected from GeneCards, TTD, DisGeNET, and KEGG. Cisplatin-related genes were downloaded from GeneWeaver. The protein-protein interaction (PPI) network was created using the STRING database. A drug-bioactive compound-disease-target network wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Our KEGG pathway analysis revealed that these targets were significantly enriched in a variety of cancer pathways, platinum drug resistance, and apoptosis pathways, interesting areas for further research. Notably, recent research found that quercetin could overcome CDDP resistance in cervical cancer cells [ 62 ]. Additionally, our previous research found that ECM can sensitize NSCLC cells to CDDP and hypersensitize CDDP-induced apoptosis in NSCLC, but the underlying mechanism was unclear [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our KEGG pathway analysis revealed that these targets were significantly enriched in a variety of cancer pathways, platinum drug resistance, and apoptosis pathways, interesting areas for further research. Notably, recent research found that quercetin could overcome CDDP resistance in cervical cancer cells [ 62 ]. Additionally, our previous research found that ECM can sensitize NSCLC cells to CDDP and hypersensitize CDDP-induced apoptosis in NSCLC, but the underlying mechanism was unclear [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 (1:1,000; ab213524; Abcam), YTHDF1 (1:1,000; ab230330; Abcam), METTL16 (1:300; orb679493; Biorbyt), ZC3H13 (1:1,000; ab70802; Abcam), and GAPDH (1:3,000; AB-M-M 001; GoodHere Technology) were purchased and used in this study. The Western blotting analysis was performed as described before (20).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Network pharmacology provides a comprehensive viewpoint, enabling an investigation of the complex network of interactions among the discovered phytochemicals and various targets within the framework of cervical cancer-related pathways. 9,10 …”
Section: Introductionmentioning
confidence: 99%